2014
DOI: 10.1111/jfb.12319
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐induced developmental plasticity of the gills and air‐breathing organ of Trichopodus trichopterus

Abstract: The air-breathing blue gourami Trichopodus trichopterus, an anabantid with a suprabranchial labyrinth organ, was used to study morphological development of respiratory systems in response to chronic hypoxia (13% O₂, combined aquatic and aerial hypoxia). Overall growth (fork length, wet mass and cutaneous surface area) of T. trichopterus did not differ between control fish and those reared in hypoxia. Both lamellar and labyrinth surface areas of the hypoxic larvae, however, increased more rapidly than controls,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 46 publications
1
31
0
Order By: Relevance
“…We studied wildcaught fish that were well acclimated to common conditions in the lab, which eliminated the influence of reversible plasticity on our results, but this approach cannot eliminate the differences between species that are caused by irreversible developmental plasticity. Developmental plasticity can have a strong influence on adult physiology (West-Eberhard, 2003; Scott and Johnston, 2012; Schnurr et al, 2014), and developmental hypoxia in particular can have persistent effects on hypoxia tolerance, the gas-exchange organs, and the activities of metabolic enzymes in several tissues (Crocker et al, 2013;Blank and Burggren, 2014;Robertson et al, 2014). Exposure of parent zebrafish to hypoxia has also been shown to improve the hypoxia tolerance of their offspring (Ho and Burggren, 2012), suggesting that trans-generational effects could have also influenced some of our observations.…”
Section: Evolution Developmental Plasticity or Parental Effects?mentioning
confidence: 99%
“…We studied wildcaught fish that were well acclimated to common conditions in the lab, which eliminated the influence of reversible plasticity on our results, but this approach cannot eliminate the differences between species that are caused by irreversible developmental plasticity. Developmental plasticity can have a strong influence on adult physiology (West-Eberhard, 2003; Scott and Johnston, 2012; Schnurr et al, 2014), and developmental hypoxia in particular can have persistent effects on hypoxia tolerance, the gas-exchange organs, and the activities of metabolic enzymes in several tissues (Crocker et al, 2013;Blank and Burggren, 2014;Robertson et al, 2014). Exposure of parent zebrafish to hypoxia has also been shown to improve the hypoxia tolerance of their offspring (Ho and Burggren, 2012), suggesting that trans-generational effects could have also influenced some of our observations.…”
Section: Evolution Developmental Plasticity or Parental Effects?mentioning
confidence: 99%
“…Nocturnal intermittent hypoxia, on the other hand, probably gave larvae sufficient time to recover and still continue subsequent development during alternate episodes of stress, recovery and normal development. Interestingly, this study found that T. trichopterus was slightly more sensitive to hypoxia in early larval life than reported for this species in an independent study (Blank & Burggren, ). There are numerous reasons for physiological variation between studies, and for fish species, the susceptibility of larvae to hypoxia can be altered by epigenetic effects relating to maternal and paternal experiences (Ho & Burggren, ; Burggren, ).…”
Section: Discussionmentioning
confidence: 99%
“…There is good evidence that vertebrate cardiovascular organs can be remodelled (Crispo and Chapman, 2010;Blank and Burggren, 2014), and cellular and biochemical mechanisms underpinning cardio-respiratory function altered (Eme et al, 2013), when oxygen supply is limited. In vertebrates, such phenotypic alterations have been shown to occur early in development and have been expressed as changes in both the activity and the timing of development of cardio-respiratory function (e.g.…”
Section: Introductionmentioning
confidence: 99%